Pretentiousness why it matters - Fox, Dan 1976- (Coffee House Press, 2016)
"Pretentiousness is for anyone who has braved being different, whether that's making a stand against artistic consensus or running the gauntlet of the last bus home dressed differently from everyone else. It's an essential ingredient in pop music and high art. Why do we choose accusations of elitism over open-mindedness? What do our anxieties about "pretending" say about us? Co-editor of Frieze, Europe's foremost magazine of contemporary art and culture, Dan Fox has authored over two hundred essays, interviews, and reviews, contributed to numerous catalogues and publications produced by major international art galleries and institutions"
Zusatz auf dem Umschlag: An essay
Keywords: Geschichte; Ästhetik; Performance; Authenticity (Philosophy); Creation (Literary, artistic, etc.); ART / Criticism & Theory; LITERARY COLLECTIONS / Essays; ART / Popular Culture; PHILOSOPHY / Aesthetics; Authentizität